Sonodynamic Therapy of Hypoxic Tumours - Beguin, E (University of Oxford, 2019)
This folder has all the raw data used to produce the results reported in the thesis "Sonodynamic Therapy of Hypoxic Tumours". The titles of subfolders indicate what type of data can be expected. This data can be opened on Excel or MATLAB for analysis.